Customer Intelligence and Customer Repurchase Behaviour in Hotels in South-West Nigeria - Nwokorie, Edwin Chigozie (Turizam, 2024)
This study examined the effect of customer intelligence on customer repurchase behaviour in hotels in South-West Nigeria. The model for the research was developed on the consequent variables of the study to test the research hypotheses. A total of 1972 copies of usable questionnaires were retrieved from customers of 160 conveniently sampled midscale and luxury hotels and used for analysis. Descriptive statistics were used to analyze the demographic elements while the One-Way ANOVA was utilized to reveal the statistical relationship between customer repurchase behaviour and the customer intelligence constructs. The linear regression model was employed to test the research hypotheses to determine significant associations and relationships between the consequent variables of the study. Results showed the effectiveness of the regression model in identifying relationships between the consequent variables, in which the four null hypotheses were rejected. The study concludes that a consideration of the factors that have a significant effect on the various dimensions of customer repurchase behaviour and the emergence of customer attrition and retention can help hotel organizations make better product marketing decisions. Recommendations include that hotels should ensure that their customer analysis is directly targeted to ensure the continuous retrieval of actual information that will directly influence business decisions